2009
DOI: 10.1016/j.taap.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's-associated Aβ oligomers show altered structure, immunoreactivity and synaptotoxicity with low doses of oleocanthal

Abstract: It now appears likely that soluble oligomers of amyloid-β 1-42 peptide, rather than insoluble fibrils, act as the primary neurotoxin in Alzheimer's disease (AD). Consequently, compounds capable of altering the assembly state of these oligomers (referred to as ADDLs) may have potential for AD therapeutics. Phenolic compounds are of particular interest for their ability to disrupt Aβ oligomerization and reduce pathogenicity. This study has focused on oleocanthal (OC), a naturallyoccurring phenolic compound found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 52 publications
3
105
0
3
Order By: Relevance
“…Alzheimer's disease) and PHF6 enables the phosphorylation of tau, thus the convalent modification of PHF6 peptide disrupts tau-tau interaction and subsequent fibril formation (Li et al, 2009) (Figure 4). Β-amyloid peptides (Aβ) are another type of lesion that are characteristic of Alzheimer's disease (Guela et al, 1998), as Aβ derived diffusible ligands (ADDLs) are neurotoxic factors proposed to instigate the onset of Alzheimer's disease (Pitt et al, 2009). Pitt and colleagues (2009) demonstrated that in vitro, oleocanthal alters the structure of ADDLs and augments antibody clearance of ADDLs, therefore protecting hippocampal neurons from ADDL toxicity.…”
Section: Oleocanthal and Neuro-degenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer's disease) and PHF6 enables the phosphorylation of tau, thus the convalent modification of PHF6 peptide disrupts tau-tau interaction and subsequent fibril formation (Li et al, 2009) (Figure 4). Β-amyloid peptides (Aβ) are another type of lesion that are characteristic of Alzheimer's disease (Guela et al, 1998), as Aβ derived diffusible ligands (ADDLs) are neurotoxic factors proposed to instigate the onset of Alzheimer's disease (Pitt et al, 2009). Pitt and colleagues (2009) demonstrated that in vitro, oleocanthal alters the structure of ADDLs and augments antibody clearance of ADDLs, therefore protecting hippocampal neurons from ADDL toxicity.…”
Section: Oleocanthal and Neuro-degenerative Diseasementioning
confidence: 99%
“…Further investigation demonstrated that oleocanthal inhibits inflammation in the same way as ibuprofen, and moreover, is substantially more potent on a equimolar basis (Beauchamp et al, 2005). Subsequent studies have shown that oleocanthal exhibits various modes of action in reducing inflammatoryrelated disease, including neuro-degenerative disease (Pitt et al, 2009, Li et al, 2009, jointdegenerative disease (Iacono et al, 2010) and specific cancers (Elnagar et al, 2011). Therefore, long term consumption of extra virgin olive oil (EVOO) containing oleocanthal may contribute to the health benefits associated with the Mediterranean dietary pattern.…”
Section: Introductionmentioning
confidence: 99%
“…11 As formas mais frequentes de βA são constituídas por 40 e 42 aminoácidos. 9,[12][13][14] Os βA formados que assumem maior comprimento têm mais facilidade para uma rápida agregação, oligomerização e formação de fibrilas. 15 A forma de oligómero é a mais neurotóxica.…”
Section: Alterações Bioquímicas Fisiológicas E Neurológicas Em Doençunclassified
“…OleA was more effective than Oleuropein and hydroxytyrosol (they are also effective but to a lesser extent) as inhibitor of Tau fibrillization [14]. OleA was also shown to modify Amyloid Precursor Protein-(APP) processing, increasing the formation of the non-amyloidogenic and neuroprotective sAPPα fragment and to decrease Aβ oligomers in HEK695 cell supernatants by increasing matrix metalloproteinase-9 (MMP-9) secretion [15]. These results are very promising and pave the way to a more extensive investigation on OleA ability to inhibit toxic amyloid aggregation of many other amyloid-associated peptides/proteins.…”
Section: Introductionmentioning
confidence: 99%